Delayed sleep-onset and biological age: late sleep-onset is associated with shorter telomere length. Issue 10 (4th July 2019) - Wynchank, Dora; Bijlenga, Denise; Penninx, Brenda W; Lamers, Femke; Beekman, Aartjan T; Kooij, J J Sandra; Verhoeven, Josine E
Abstract: Study Objectives: We evaluated the relationship between leukocyte telomere length (LTL) and sleep duration, insomnia symptoms, and circadian rhythm, to test whether sleep and chronobiological dysregulations are associated with cellular aging. Methods: Data from the Netherlands Study of Depression and Anxiety ( N = 2, 936) were used at two waves 6 years apart, to measure LTL. Telomeres shorten during the life span and are important biomarkers for cellular aging. LTL was assessed by qualitative polymerase chain reaction and converted into base pair number. Sleep parameters were: sleep duration and insomnia symptoms from the Insomnia Rating Scale. Circadian rhythm variables were: indication of Delayed Sleep Phase Syndrome (DSPS), mid-sleep corrected for sleep debt on free days (MSFsc), sleep-onset time, and self-reported chronotype, from the Munich Chronotype Questionnaire. Generalized estimating equations analyzed the associations between LTL, sleep, and chronobiological factors, adjusted for baseline age, sex, North European ancestry, and additionally for current smoking, depression severity, obesity, and childhood trauma. Results: Indicators of delayed circadian rhythm showed a strong and consistent effect on LTL, after adjustment for sociodemographic and health indicators. Late MSFsc ( B = −49.9, p = .004), late sleep-onset time ( B = −32.4, p = .001), indication of DSPS ( B = −73.8, p = .036), and moderately late chronotype in adulthood ( B = −71.6, p = .003) were associated with significantly shorter LTL across both waves; whereas sleep duration and insomnia symptoms were not. Extremely early chronotype showed significantly less LTL shortening than intermediate chronotype ( B = 161.40, p = .037). No predictors showed accelerated LTL attrition over 6 years. Conclusions: Individuals with delayed circadian rhythm have significantly shorter LTL, but not faster LTL attrition rates.